User-friendliness of the pain assessment in impaired cognition (PAIC15) in persons with aphasia: a pilot study - Neeltje J. de Vries; Hanneke J. A. Smaling; Jenny T. van der Steen; Wilco P. Achterberg (Future Science OA)
Background Persons with aphasia have difficulties communicating pain symptoms.Methods Thirteen observers performed multiple observations using the Pain Assessment in Impaired Cognition (PAIC15) scale for persons with aphasia during rest and transfer in persons with aphasia. This pilot study examined the user-friendliness of PAIC15 and preference for type of self-report pain scales with a questionnaire.Results The PAIC15 was considered user-friendly for persons with aphasia: items were clear and not difficult to score. When self-report is possible, the combined scale with verbal, visual, and numerical elements is preferred for persons with aphasia.Conclusion PAIC15 is a helpful instrument to aid clinical judgment and to screen for the presence of pain in persons with aphasia. There were mixed opinions, but most observers preferred to use the combined self-report scale for persons with aphasia.